Influencing Factors of the Informal Investment in Central Europe - Györfy, Lehel; Madaras, Szilárd (Economics and Business, 2020)
This paper examines the influencing factors of becoming informal investors in two groups of Central European countries: the innovation-driven (Estonia, Latvia, Slovenia and Slovakia) and efficiency-driven economies (Croatia, Hungary, Lithuania, Poland and Romania), based on the GEM (Global Entrepreneurship Monitor) database from 2014. According to the results, in the studied innovation-driven economies of Central Europe the probability of becoming an informal investor is higher for those, who know other entrepreneurs, who are confident in their own entrepreneurial skills, who are in the higher percentile of the household income, who are older and male. The results also suggest that in the studied efficiency-driven economies of Central Europe the probability of becoming an informal investor is higher for those who are confident in the own entrepreneurial skills, who know other entrepreneurs, who are in the higher percentile of the household income, who are older and male. The probability is decreased, if somebody is employed full-time. The study emphasises similarities instead of differences regarding the analysed aspect between the two groups of countries.